Therapeutic targeting of tumor spheroids in a 3D microphysiological renal cell carcinoma-on-a-chip system - Miller, Chris P.; Fung, Megan; Jaeger-Ruckstuhl, Carla A.; Xu, Yuexin; Warren, Edus H.; Akilesh, Shreeram; Tykodi, Scott S. (Neoplasia (New York, N.Y.), 2023)
Metastatic renal cell carcinoma (RCC) remains an incurable disease for most patients highlighting an urgent need for new treatments. However, the preclinical investigation of new therapies is limited by traditional two-dimensional (2D) cultures which do not recapitulate the properties of tumor cells within a collagen extracellular matrix (ECM), while human tumor xenografts are time-consuming, expensive and lack adaptive immune cells. We report a rapid and economical human microphysiological system (“RCC-on-a-chip”) to investigate therapies targeting RCC spheroids in a 3D collagen ECM. We first demonstrate that culture of RCC cell lines A498 and RCC4 in a 3D collagen ECM more faithfully reproduces the gene expression program of primary RCC tumors compared to 2D culture. We next used bortezomib as a cytotoxin to develop automated quantification of dose-dependent tumor spheroid killing. We observed that viable RCC spheroids exhibited collective migration within the ECM and demonstrated that our 3D system can be used to identify compounds that inhibit spheroid collective migration without inducing cell death. Finally, we demonstrate the RCC-on-a-chip as a platform to model the trafficking of tumor-reactive T cells into the ECM and observed antigen-specific A498 spheroid killing by engineered human CD8+ T cells expressing an ROR1-specific chimeric antigen receptor. In summary, the phenotypic differences between the 3D versus 2D environments, rapid imaging-based readout, and the ability to carefully study the impact of individual variables with quantitative rigor will encourage adoption of the RCC-on-a-chip system for testing a wide range of emerging therapies for RCC.